Penyuluhan Perilaku Hidup Bersih Dan Sehat (PHBS) Di Dusun Berjo Wetan Godean Sleman Yogyakarta - Dian Wuri Astuti; Fitri Nadifah; Yuliana Prasetyaningsih; Vixa Meindara; Anggraeni; Diah Irawati; May Tri Mulyani (J.Abdimas: Community Health, 2020)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve an optimal health degree for everyone. Cultivating a healthy lifestyle in society must be initiated and worked on from oneself. Meanwhile, public awareness of health and hygiene and healthy lifestyles, especially rural communities is still very low. For this reason, presenting counseling is expected to increase public knowledge and awareness of the importance of making clean and healthy living behaviors (PHBS) in daily life so that a better health degree can be realized.